Ebselen, a promising host-directed therapeutic option against Yersinia pseudotuberculosis infection - Wu, Zhongbao; Tang, Lu; Wang, Yueqing; Ndong Ella, Emmanuelle Vladia; He, Jing; Cheng, Chuang; Xiao, Lin; Wang, Yalan; Dong, Chuanjiang; Zou, Lili; Wang, Jun (Frontiers in Microbiology, 2026)
BackgroundAs a prevalent food-borne zoonotic pathogen, Yersinia pseudotuberculosis (Y. pseudotuberculosis) can lead to severe health issues in both animals and humans. At present, therapeutic options are quite limited. This study evaluated the pharmacological properties of ebselen (EbSe) and its potential as a host-directed therapy (HDT) against Y. pseudotuberculosis infection. EbSe has shown efficacy and safety in clinical settings, particularly against Gram-positive bacteria, as evidenced by its pharmacological properties and clinical applications; however, its efficacy against Gram-negative bacteria remains poorly characterized.MethodsTo systematically elucidate the mechanism of Ebse efficacy, an in vivo mouse model of acute gastroenteritis induced by Y. pseudotuberculosis and an in vitro macrophage-bacteria interaction model were established. Monitoring mouse survival rates and bioluminescence imaging analysis revealed Ebse’s ability against Y. pseudotuberculosis infection. Flow cytometry characterized peritoneal macrophage polarization types and in vitro ones. Transcriptome analysis identified differentially expressed mRNAs in macrophages post-Y.pseudotuberculosis infection, validated by real-time quantitative PCR (RT-qPCR). Cell death was assessed using the CCK-8 assay and propidium iodide (PI) staining, supplemented by morphological observation via transmission electron microscopy (TEM). The intracellular bacteria were quantified through Cytation 5 imaging and fluorescent quantification. Cellular reactive oxygen species (ROS) production was measured by flow cytometry, while glutathione (GSH) content was determined using a micro-reduction GSH assay kit. Intracellular thioredoxin reductase 1 (Txnrd1) activity was assessed via the 5,5’-dithiobis(2-nitrobenzoic acid) (DTNB) assay, with protein expression levels detected by Western blot.Results and discussionEbSe improved overall survival and reduced bacterial burden in mice with gastroenteritis. EbSe was found to modulate macrophage polarization, inhibiting apoptosis and excessive inflammation, as detailed in macrophage function and their role in inflammatory responses. Furthermore, EbSe has been shown to protect Raw264.7 cells from Y. pseudotuberculosis-induced death by enhancing antioxidant defenses. This is evidenced by a reduction in intracellular reactive oxygen species levels and an elevation in glutathione concentrations, and increased thioredoxin reductase 1 activity. Collectively, these findings suggest that EbSe enhances the host resistance to Y. pseudotuberculosis infection, likely through immunomodulatory effects rather than direct antibacterial activity against Gram-negative bacteria.